EFFICIENCY OF DIFFERENT LEVELS OF L-CARNITINE SUPPLEMENTATION ON GROWTH PERFORMANCE AND BLOOD PARAMETERS IN THREE LINES OF KURDISH QUAILS (COTURNIX COTURNIX) - Lina S. Mahdi; Lajan S. Ahmed; Parizan W. Ibrahim; Gulstan H. Radha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to assess the impact of genetic groups (comprising three distinct lines of Kurdish quails, which are desert, brown, and white), graded levels of L-carnitine and their interaction on the performance of growth traits and blood parameters. For this purpose, the same basic diet was given to 480 Kurdish quail chicks one day old, which was then supplemented for two to seven weeks of age with 0 (control), 150, 350, or 550 mg of L-carnitine per kg of diet. The statistical analysis showed that the lines, L-carnitine supplementation, and their interaction had a significant (p≤0.01) impact on the Kurdish quail’s blood parameters, feed intake, feed conversion ratio, body weight, and body weight gain. The desert lines exhibited significantly higher growth performance values in all weeks. Furthermore, supplementation with 350 and 550 mg/kg L-carnitine throughout the experimental period significantly improved these characteristics compared to the control group, with the other experimental treatment (150 mg L-carnitine/kg diet) having the highest values. As well as for the interacted groups, the desert lines with diet of 350 mg/kg L-carnitine had significant influence on body weight, and weight gain. On the other hand, the white lines with a diet of 350 mg/kg L-carnitine showed significantly (P≤0.01) better feed intake and better feed conversion ratio than all other treatments in the same period. It was concluded that L-carnitine supplementation at 350 and 550 mg/kg was sufficient to improve growth characteristics and blood parameters in Kurdish quail lines.